2021
DOI: 10.21037/cdt-20-771
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of Ebstein’s anomaly beyond childhood: Imaging, surgery, and future perspectives

Abstract: Ebstein's anomaly is a rare congenital heart disease with malformation of the tricuspid valve and myopathy of the right ventricle. The septal and inferior leaflets adhere to the endocardium due to failure of delamination. This leads to apical displacement of their hinge points with a shift of the functional tricuspid valve annulus towards the right ventricular outflow tract with a possibly restrictive orifice. Frequently, a coaptation gap yields tricuspid valve regurgitation and over time the "atrialized" port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…The literature reports that cyanosis, dyspnea and poor exercise tolerance to be key symptoms among patients with EA. 25 Cyanosis is reported in almost half of EA patients while studies have reported that severe cyanosis is further related to poor exercise intolerance. 26,27 Chest pain and syncope are the other commonly reported symptoms by other researchers in the past.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports that cyanosis, dyspnea and poor exercise tolerance to be key symptoms among patients with EA. 25 Cyanosis is reported in almost half of EA patients while studies have reported that severe cyanosis is further related to poor exercise intolerance. 26,27 Chest pain and syncope are the other commonly reported symptoms by other researchers in the past.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it can even save a child's life if left untreated. After surgery, children typically need to stay in the hospital for several days for monitoring and recovery before they can go home [29].…”
Section: Aetiologies Of Cardiac Surgery In Childrenmentioning
confidence: 99%